Intramuscular innervation of plantaris muscle evaluated using a modified Sihler's staining protocol — Proposal for a new classification - Olewnik, Ł.; Karauda, P.; Gonera, B.; Kurtys, K.; Haładaj, R.; Tubbs, R. Shane; Paulsen, Friedrich; Ramón Sanudo, J.; Polguj, M. (Annals of Anatomy-Anatomischer Anzeiger, 2020)
Purpose: The plantaris muscle is a morphologically variable structure with regard to both its origin and insertion, and the course of the tendon. We here determined the pattern of branching and distribution of intramuscular nerves of the plantaris muscle to determine its usability for autologous transplantation. No information exists on the innervation of the plantaris muscle using Sihler's staining technique, and hence its intramuscular nerves. The main purpose of the work is to determine the pattern of branching and distribution of the intramuscular nerves of the plantaris muscle. Is the plantaris muscle a good transplant candidate? Materials and methods: Eighty lower limbs from cadavers (40 left, 40 right, 40 male, 40 female, age range 41–94 years) were fixed in 10% formalin solution and examined macroscopically as well as morphometrically with regard to the innervation pattern of the respective plantaris muscle. Afterwards Sihler's staining was used in all 80 plantaris muscles to identify the exact distribution of the muscular branch originating from the main nerve trunk in the muscle belly. Results: Two patterns of branching and nerve distribution could be intensified in the plantaris muscle: Type I, with a single pattern entire up to the muscle and then divided into superior and inferior intramuscular branches.; type II with a double innervation pattern (superior and inferior). The superior and inferior pattern were not connected to each other. Conclusion: The plantaris muscle reveals variability with two different innervation patterns. Type II is ideally suited for autologous transplantation. New classifications of innervation are desirable for individual muscles rather than a generalized approach.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Innervation; Nerve; Planteris muscle; Sihler's staining